The Influence of Hotel Service Quality, Occupancy Rate, and Guest Voice towards Customer Satisfaction at Hotel under Marriott Company - Angel; Jessica Acadia; Catherine Colleen; Jes Slyn; James (International Journal of Economics, Business Management and Accounting (IJEBMA), 2020)
This study investigates the intricate dynamics of hotel service quality, occupancy rates, and guest feedback within the context of Marriott Company-operated hotels and their collective influence on customer satisfaction. Through a multifaceted research approach encompassing guest surveys, occupancy rate analysis, and staff interviews, we uncover the fundamental significance of service quality in shaping guest satisfaction. Additionally, we illuminate the delicate balance between occupancy rates and service quality, shedding light on how high occupancy can be harnessed for operational benefits while preserving service excellence. Importantly, this research underscores the pivotal role of guest voice in enhancing satisfaction, emphasizing Marriott's commitment to feedback mechanisms as a potent tool for continual improvement. These findings offer valuable insights for Marriott and the broader hospitality industry, emphasizing the need for a comprehensive approach to service management that acknowledges and optimizes these interconnected elements to foster enduring customer satisfaction